2023
DOI: 10.1111/os.13823
|View full text |Cite
|
Sign up to set email alerts
|

Valgus Stress Radiograph Can Predict Alignment Change of Medial Mobile‐Bearing Unicompartmental Knee Arthroplasty

Abstract: Objective Finding reliable tools to predict alignment change after medial mobile‐bearing unicompartmental knee arthroplasty (UKA) can help surgeons avoid under‐ or over‐correction. This prospective study aimed to investigate whether the parameters related to medial collateral ligament tension on valgus stress radiograph can predict the alignment change of medial mobile‐bearing UKA and establish a prediction model. Methods This study prospectively included the patients undergoing medial mobile‐bearing UKA for k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that preoperative valgus stress radiographs could be used to predict postoperative alignment, particularly for UKA [7,9,10,30]. Slaven et al reported that knees with varus alignment as overcorrection after UKA developed lateral TF joint OA, while those with residual excessive varus alignment had early implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that preoperative valgus stress radiographs could be used to predict postoperative alignment, particularly for UKA [7,9,10,30]. Slaven et al reported that knees with varus alignment as overcorrection after UKA developed lateral TF joint OA, while those with residual excessive varus alignment had early implant failure.…”
Section: Discussionmentioning
confidence: 99%